PENGEMBANGAN LKPD BERBASIS HAPPY NOTE GALAXY MATA PELAJARAN IPAS UNTUK PESERTA DIDIK KELAS VI A SD NEGERI 7 KAMPUNGDALEM - Cahyani, Lala Tri; Frita Devi Asriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science and Social Studies (IPAS) learning in elementary schools is still perceived as abstract, and students often struggle to comprehend the material due to the lack of engaging and age-appropriate teaching resources. This study adopts a Research and Development (R&D) approach, aiming to develop Happy Note Galaxy-based Student Worksheets (LKPD) for the IPAS subject, specifically on the Solar System topic, for sixth grade students at SD Negeri 7 Kampungdalem. The development model used is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research instruments included validation sheets and response questionnaires from both students and teachers. Validation by subject matter and media experts confirmed that the LKPD was highly valid, with average scores of 90.6% (content validation) and 86.5% (media validation). The implementation of the LKPD among 20 students yielded highly positive feedback: 90% of students and 100% of teachers found the worksheets highly engaging and easy to understand. The developed LKPD incorporates visual elements and problem-based activities, aligning with the Problem-Based Learning (PBL) model to foster active student participation. Based on the findings, it can be concluded that the Happy Note Galaxy-based LKPD meets the feasibility criteria as an innovative alternative teaching material, effectively enhancing students’ nterest and comprehension of the Solar System topic.